Personality as a Driver of Consumer Fair Trade Engagement and Ethically-Minded Behavior - Kutaula, Smirti; Gillani, Alvina; Leonidou, Leonidas C.; Christodoulides, Paul (My University, 2019)
We develop and test a conceptual model, anchored on Cognitive Affective Personality System theory, examining how consumer personality traits impact engagement with fair trade issues, and subsequent ethically-minded behavior. Based on a survey among 323 consumers, it was revealed that extraversion, agreeableness, and conscientiousness positively affect consumer fair trade engagement, neuroticism has a negative effect, while openness has no significant impact. Moreover, the fair trade engagement of a consumer was found to strongly predict his/her ethically-minded behavior. Furthermore, our findings indicate a stronger association between consumer fair trade engagement and ethically-minded behavior in the case of older, more educated and high income consumers, while gender played no moderating role.
Keywords: Cognitive Affective Personality System theory; consumer personality